Revascularization in left ventricle dysfunction - Godoy-Palomino, Armando L. (2021)
Left ventricular dysfunction due to adverse remodeling constitutes the underlying structural anatomical condition of heart failure and is the main and most severe sequela of long-term coronary artery disease, and it is the only pathology that can benefit from surgical myocardial revascularization. For its control, there are current medical treatment guidelines supported by the favorable results of contemporary clinical trials. However, in recent studies, there was no benefit of surgical revascularization in addition to optimal medical therapy when compared to optimal medical therapy alone. The identification of myocardial viability to guide revascularization was also not favorable. The results of the extension of these trials showed benefit of revascularization treatment, but the detection of viability remained unfavorable. Increased left ventricular ejection fraction, as a marker of benefit from revascularization, was not associated with lower mortality. There are many reasons why the known advantages of revascularization were not identified. Despite this discrepancies, myocardial revascularization and the identification of viability in these patients are supported and are usually indications for routine treatment.